Integration of Education and Science: Historical Aspect (Pedagogy of Higher and Secondary Education, 2016)
Vakulenko V. N. Integration of Education and Science: Historical Aspect.Historical pre-conditions of integration of education and science are considered in the article and analysed. Theoretical pre-conditions of integration have been defined and phenomenon of integration of education and science has been understood. Визначенно The essence of integration has been determined, and integration has been examined as an integrity of processual and result constituents.The specific of integration of national education and science that in a great deal differs from European educational and scientific tradition is examined in the history of education. The national processes of integration of education and science closely link with historical traditions, and therefore they determine direction and specificity of the development of education and science in Ukraine. The feature of national scientific tradition is in its fundamental dialectical position on the basis of the theory of cognition as a theory of reflection unlike western metaphysical position on the basis of the theory of cognition as a theory of representation.With main essential features of education and research follows a number of other integration: dialogic, latency, multidimensionality, adaptability, manageability.The main role of science in education is to be a stimulus, the driving force behind the operation and development of education, and the basic role of education in the science presented in the preservation and transmission of all established science in shaping the experience of traditional knowledge.
Keywords: integration; science; education; educationally-scientific integration